2017
DOI: 10.1016/j.commatsci.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

A paramagnetic neutral CBVN center in hexagonal boron nitride monolayer for spin qubit application

Abstract: First-principles calculations in combination with group theory analyses were employed to study the spin-polarized electronic structures of C B V N centers consisting of a nitrogen vacancy and a substitutional carbon atom in hexagonal boron nitride (h-BN) monolayer with different charge states.It is clarified that the paramagnetic neutral C B V N center is stable in the n-type h-BN monolayer. The neutral defect center possesses a triplet (S=1) ground state and with two spin-conserved optical vertical transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…7(a). This leads to miss-assignment of the ground state of the VNCB which was predicted to be triplet in character 150 , whilst we found that the singlet ground state is lower in energy compared to the lowest triplet state by ~1 eV, after applying the correction factors. Therefore, similar approach should be adopted on other defects to have an energetically useful comparison with experiment.…”
Section: Major Theoretical/computational Challengesmentioning
confidence: 76%
“…7(a). This leads to miss-assignment of the ground state of the VNCB which was predicted to be triplet in character 150 , whilst we found that the singlet ground state is lower in energy compared to the lowest triplet state by ~1 eV, after applying the correction factors. Therefore, similar approach should be adopted on other defects to have an energetically useful comparison with experiment.…”
Section: Major Theoretical/computational Challengesmentioning
confidence: 76%
“…In recent years, advanced calculations based on hybrid density functional theory have provided considerable insight into the defect properties of III-nitrides [28][29][30]. A number of previous studies have addressed native point defects or impurities in h-BN using first-principles calculations [31][32][33][34][35][36]. However these studies all had shortcomings, such as being based on less accurate functionals, not considering all possible spin configurations, or not including proper finite-cellsize corrections (the latter being very important for the energetics of charged defects).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is observed that the emitters can be created by ion bombardment in a controlled fashion 46 . More recently, several DFT computational analyses have attributed the emissions to charge neutral native and substitutional defects with deep band-gap energy levels 25,47,48 . These reports lay the ground work for further research on the physics of such defects.…”
Section: Introductionmentioning
confidence: 99%